Ocular Surface Inflammatory Disorders (OSID): A Collective of Systemic Etiologies Which Cause or Amplify Dry Eye Syndrome - Soifer, Matias; Azar, Nadim S.; Mousa, Hazem M.; Perez, Victor L. (Frontiers in Medicine, 2022)
The ocular surface inflammatory disorders (OSID) are caused by systemic disorders that conduct a persistent inflammatory reaction in the ocular adnexal connective tissues, such as the conjunctiva, lacrimal gland (LG) and meibomian glands (MGs), which concludes with destabilization of the tear film and corneal epithelial erosions. The etiologies of OSID are a subset of systemic pathologies that cause an inflammatory dry eye syndrome, such as graft versus host disease, Sjögren’s syndrome, allergies, cicatrizing conjunctivitis and more. This causes dry eye syndrome as a consequence of the persistent surrounding inflammation in the adnexal tissues, which is distinct from the age-related dry eye disease. A limitation towards management of these conditions is the lack of available biomarkers that can detect presence of inflammation and quantify damage on the conjunctiva and LG, even though these are considered to be drivers of the inflammatory milieu. The OSID and dry eye syndrome are caused by different immune cells which are not exclusively limited to T cell lymphocytes, but rather derive from an orchestrated multicellular immunologic response. Recognition of this syndrome is crucial to direct research in a direction that clarifies the potential role of inflammation and its associated immune phenotype on the conjunctiva and adnexal ocular tissues in OSID and dry eye syndrome. On this paper, we review the basic and clinical research evidence for the existence of OSID with focus on the different immune cells involved, the target tissues and potential consequences and OSIDs diagnostic and therapeutic implications.